Poverty, equality, and growth : the politics of economic need in postwar Japan - Milly, Deborah J., 1952- (Harvard East Asian monographs, 1999)
"In the early 1950s, many Japanese lived in poverty. Today only a handful do. This book explains why and how the postwar Japanese state progressed from employing responses to poverty preferred in the prewar era to adopting equality as the basis for a social compromise. The author argues that to account for why political actors succeeded in crafting a program that won acceptance, it is necessary to look beyond their interests and to identify how they relied on knowledge and normative arguments."--Jacket